(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Volleyball is a sport that requires mastery of fundamental techniques and adequate physical abilities to achieve optimal performance. One of the most important basic techniques is the overhead pass, which plays a crucial role in controlling the ball and organizing offensive play. However, many students experience difficulties in performing effective overhead passes due to insufficient pushing strength and limited technical proficiency. Therefore, innovative training methods are needed to improve overhead passing performance. This study aimed to determine the effect of an upper passing training method using a basketball on upper passing force strength and overall overhead passing performance in volleyball. This study employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest model. The participants were 15 members of the Bimantara Volleyball Club selected through purposive sampling. Data were collected using an observation sheet and an overhead passing skill test consisting of five assessment indicators: body position and balance, finger-contact accuracy, passing strength and distance, directional accuracy, and movement coordination. Data were analyzed using descriptive statistics, normality tests, and paired-samples t-tests. The results showed a significant improvement in participants’ overhead passing performance following the intervention. The mean score increased from 40.00 in the pretest to 65.33 in the posttest, representing an improvement of 25.33 points. The paired-samples t-test revealed a statistically significant difference between pretest and posttest scores (t = -3.833; p = 0.002 < 0.05). In conclusion, the upper passing training method using a basketball is effective in improving upper passing force strength and overall passing performance. The use of a heavier training medium provides additional overload that enhances muscular strength, movement efficiency, and technical execution during overhead passing.